Sexual Harassment and Academic Engagement of Female Students in Higher Education Institutions in Nigeria - Dorothy Ebere Adimora; Janefrances Chinenye Adimora (European Scientific Journal, ESJ, 2026)
Sexual harassment in higher education has become an increasingly global concern with significant implications for students’ well-being and academic success. This study explored the impact of sexual harassment (SH) on the academic engagement of female students in Higher Education Institutions (HEIs) in Nigeria. Specifically, the study examined (1) the forms and contexts of SH experienced by female students and (2) analysed how these experiences influence their academic engagement across the cognitive, affective, and behavioural domains. The normalisation of gender-based violence (GBV), toxic academic masculinity, a culture of silence, and a lack of active leadership were identified as key features that enable SH in HEIs and contribute to academic disengagement among female students. A qualitative phenomenological case study design using in-depth interviews was employed for data collection, and students’ narratives were thematically analysed. The findings revealed that SH significantly undermines students’ academic engagement across all domains. Participants reported reduced emotional connection to learning (affective), withdrawal from academic activities (behavioural), and difficulties with concentration, comprehension, and task completion (cognitive). These challenges manifested as reluctance to participate in class discussions, difficulty completing assignments and presentations, fear, loss of motivation, and negative perceptions of the academic environment, including relationships with lecturers and peers. The study further shows that institutional factors such as weak reporting mechanisms, fear of stigmatisation, and prolonged complaint procedures function as structural barriers that discourage reporting and reinforce silence. Consequently, legal action against perpetrators was rarely pursued. Generally, the study indicates that sexual harassment operates not only as an experience but also as a structural constraint on students’ ability to engage meaningfully with their education. It shows the need for institutional reforms that promote safe learning environments, strengthen reporting systems, and support affected students’ academic recovery.